Evaluative vocabulary as a method for quality presentation in advertising of children's products - E.A. Vazhdaeva (Ученые записки Казанского университета: Серия Гуманитарные науки)
The functioning of lexemes with evaluative semantics in the texts of advertising of products for children aged from 0 to 3 years was analyzed. The study is highly relevant, because the evaluative vocabulary of advertising has been poorly studied. We identified the most typical evaluative lexemes of different parts of speech and their types indicating the quality of the advertised product. The relations between the product group and the evaluative semantics of lexemes were considered. The following main methods were used during the study: continuous sampling, content analysis, description, and comparison. A number of examples were provided to prove that evaluative vocabulary is successfully used in advertising texts to present the product quality. The highest frequency of use in the texts of children products’ advertising was found for nouns of general value with diminutive suffixes, adjectives, and adverbs that characterize both the product and its consumer. Lexemes with the semantics of special value, which expresses the brand and consumer values, as well as related to the sense, taste, and tactile perception were also common. Lexemes with such semes as smell, weight, and visual perception were rarely used. Lexemes with the normative and teleological evaluative components were specific. The results obtained are important for the theory and practice of advertising communication and can be used to successfully design new and effective advertising.